Food, Health and Safety in Cross Cultural Consumer Contexts - Byrne, Derek V. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The concept of cross-cultural perspectives in research in food is important in general and particularly so in relation to human perception in food and health. Food concepts are very different across different jurisdictions. Different markets and cultures have varying perspectives on what is considered a palatable, acceptable, or useful food or food product; in simple terms, one size does not at all in the majority of cases. Specific markets thus need targeted food design, to be successful from a myriad of perspectives. In this Special Issue anthology "Food, Health and Safety in Cross-Cultural Consumer Contexts", we bring together articles that show the wide range of studies from fundamental to market applicability currently in focus in sensory and consumer science in food, health, and safety cross-cultural contexts. From the included perspectives, it is abundantly clear that there is a need for much knowledge related to future food design linked to cross-cultural contexts and that this will continue to be critical to the success of food transfer in global food markets.